2012
DOI: 10.1249/mss.0b013e318262cb17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Preconditioning on Lactate Accumulation and Running Performance

Abstract: IPC improves 5-km time trial performance in healthy male individuals. Moreover, we found that IPC is associated with an attenuated rise in blood lactate concentration at submaximal level during an incremental running test. This could indicate that IPC allows for higher work rates and thus improves time trial performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
192
4
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(225 citation statements)
references
References 29 publications
17
192
4
9
Order By: Relevance
“…Each leg was exposed to 5 min of occlusion with the cuff inflated to 220 mmHg (IP) or 50 mmHg (CON), followed by 5 min of reperfusion and rest for 4 consecutive cycles, as has previously been shown to be effective (Jean-St-Michel et al 2011;Bailey, Jones, et al 2012). An overview of the preconditioning protocol and subsequent graded exercise test (GXT) is shown in Figure 1.…”
Section: Ischaemic Preconditioningmentioning
confidence: 99%
See 3 more Smart Citations
“…Each leg was exposed to 5 min of occlusion with the cuff inflated to 220 mmHg (IP) or 50 mmHg (CON), followed by 5 min of reperfusion and rest for 4 consecutive cycles, as has previously been shown to be effective (Jean-St-Michel et al 2011;Bailey, Jones, et al 2012). An overview of the preconditioning protocol and subsequent graded exercise test (GXT) is shown in Figure 1.…”
Section: Ischaemic Preconditioningmentioning
confidence: 99%
“…Few studies have considered endurance running, however Bailey, Jones, et al (2012) reported lower blood lactate concentration (mean difference -1.07 mMol.L -1 ) throughout an incremental submaximal running test, although no subsequent effect on maximum oxygen consumption (V" O 2max ) was observed. This was followed by improved 5 km running time with a mean improvement of 34 s (2.5%, p=0.03), highlighting the potential for use prior to endurance running.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O tempo ideal entre o fim da manobra (IPC) e o início do teste ainda não é consenso e varia entre 5 e 90 minutos na maioria dos estudos relacionados ao desempenho 8 . Apesar disso, autores sugerem que o efeito ergogênico agudo ocorreria dentro de 45 minutos a partir do fim da manobra 8,11,12 .…”
Section: O Que é Ipc?unclassified